1998
DOI: 10.1111/1467-8411.t01-1-00039
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Investment in East Asia: A Survey

Abstract: This article updates the May 1989 literature survey on foreign direct investment (FDI) in the East Asian region published in this journal. Following an overview of trends of FDI in the 1990s, it focuses on three key issues: the impact of the recent Asian economic crisis on FDI inflow relative to other forms of capital inflows; the link between FDI and trade; and technology transfer and adaptation. It is too early to discern the implications of the crisis for host-country policies and investment decisions of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…New investments into ASEAN countries were still at relatively high levels even in the wake of the Asian financial crisis, and most relocations from ASEAN countries to China in recent years have not involved full factory closures, but relocations of manufacturing of specific (low-end) products. This finding is consistent with earlier studies (Hill and Athukorala, 1998;JETRO, 2002;Wu and Puah, 2002), and shows the reluctance of foreign firms to completely withdraw from a host country once they have entered it, even if conditions become less favorable for specific manufacturing operations. This can be understood as the willingness of these firms to maintain investments as a 'real option' in the location facing uncertainty regarding future economic conditions (Kogut and Kulatilaka, 1994), or for possible upgrading of existing production bases (Belderbos and Zou, 2004;Song, 2002).…”
Section: Conclusion and Policy Implicationssupporting
confidence: 92%
“…New investments into ASEAN countries were still at relatively high levels even in the wake of the Asian financial crisis, and most relocations from ASEAN countries to China in recent years have not involved full factory closures, but relocations of manufacturing of specific (low-end) products. This finding is consistent with earlier studies (Hill and Athukorala, 1998;JETRO, 2002;Wu and Puah, 2002), and shows the reluctance of foreign firms to completely withdraw from a host country once they have entered it, even if conditions become less favorable for specific manufacturing operations. This can be understood as the willingness of these firms to maintain investments as a 'real option' in the location facing uncertainty regarding future economic conditions (Kogut and Kulatilaka, 1994), or for possible upgrading of existing production bases (Belderbos and Zou, 2004;Song, 2002).…”
Section: Conclusion and Policy Implicationssupporting
confidence: 92%
“…Many studies have raised the question whether FDI contributes to employment generation and a reduction of labor market problems in a country. Hill and Athukorala (1998) in their research "Foreign Investment in East Asia: A Survey" have shown that FDI's impact on the host country has been generally favorable in most developing countries since there have been visible positive impact on the creation of jobs in sectors attracting FDI inflows and occasionally in supportive domestic industries. Also, Buffie (1993) assessed the impact of foreign investment on underemployment in a two-sector dual economy model.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, manufacturing FDI brings with it many of the valuable technology transfer effects increasingly sought, partly as a consequence of the Asian crisis, by emerging economies in the region (Balasubramanyam and Salisu 1999). Indeed, Asia-Pacific countries are having increasingly to compete for FDI from MNCs, with countries both from within and without the region (Haaland 1999;Hill 1998). Hence, manufacturing MNCs' views concerning the Asian crisis are of considerable interest.…”
Section: Introductionmentioning
confidence: 99%